Emotional and behavioural difficulties in mainstream schools - Visser, John, 1946-; Daniels, Harry; Cole, Ted. (Amsterdam ; New York : JAI, 2001)
Drawing upon research and practice in a number of countries, the contributors to this volume describe advances in meeting the needs of children and young people with emotional and behavioural difficulties. Following the Salamanca agreement and other international treaties, sovereign states are pursuing, at different rates, a more inclusive educational agenda. There is concern for those pupils who are excluded and in danger of becoming increasingly marginalized in their societies as their engagement in education decreases. Foremost amongst these pupils are those with emotional and behavioural difficulties. The issues surrounding their inclusion in education, particularly mainstream education, are explored, along with the factors that contribute to successful interventions. Contributors from Spain, Norway, Australia, Canada, Finland and the United Kingdom describe ways of meeting their emotional and behavioural needs within education. The authors raise factors, which could contribute towards greater inclusive practice.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Mainstreaming in education; Behavior disorders in children; Classroom management; Teaching of students with emotional & behavioural difficulties; Schools; Education -- Special Education -- General